Strategic Model of the Mother’s Qur’anic Teaching Movement (GINN) in Improving Children’s Qur’anic Literacy Through the Role of Mothers as the First Madrasa in Aisyiyah, Sukabumi Regency - Tetty Sufianty Zafar; Abdul Bari; Abielya Athaya; Husnul Khatimah Aulia (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Abstract. Pengabdian ini bertujuan mengembangkan model strategis pemberdayaan ibu dalam meningkatkan kompetensi pedagogis ibu sebagai pendidik utama di lingkungan keluarga sekaligus memperkuat kemampuan membaca Al-Qur'an anak usia sekolah di Kabupaten Sukabumi. Program dilaksanakan dengan pendekatan pendidikan berbasis komunitas anggota organisasi perempuan Islam Aisyiyah sebagai subjek utama perubahan. Peserta membentuk kelompok belajar komunitas beranggotakan lima hingga sepuluh anak yang aktif menyelenggarakan sesi pembelajaran dua kali per pekan selama enam bulan. Analisis data dilakukan secara deskriptif kuantitatif melalui instrumen penilaian kemampuan membaca, evaluasi hafalan, observasi perilaku, dan skala kepercayaan diri mengajar. Hasil kegiatan menunjukkan peningkatan kemampuan membaca Al-Qur'an anak sebesar 57 persen, kemajuan level membaca 70 persen, dan peningkatan hafalan 133 persen. Kepercayaan diri ibu dalam mengajar meningkat 65 persen, dengan 80 persen peserta menyatakan kesiapan sebagai instruktur komunitas. Program ini terbukti membentuk model pemberdayaan yang berkelanjutan dan dapat direplikasi dalam jaringan pendidikan keagamaan berbasis Masyarakat. Abstract. This community service project aims to develop a strategic model for empowering mothers to enhance their pedagogical competencies as primary educators within the family, whilst simultaneously strengthening the ability of school-age children in Sukabumi Regency to read the Qur’an. The programme was implemented using a community-based educational approach, with members of the Islamic women’s organisation Aisyiyah serving as the primary agents of change. Participants formed community learning groups comprising five to ten children, which actively organised learning sessions twice a week for six months. Data analysis was conducted using quantitative descriptive methods through assessment tools for reading ability, memorisation evaluation, behavioural observation, and a teaching confidence scale. The results of the activity showed a 57 per cent improvement in the children’s ability to read the Qur’an, a 70 per cent improvement in reading level, and a 133 per cent improvement in memorisation. Mothers’ confidence in teaching increased by 65 per cent, with 80 per cent of participants expressing their readiness to serve as community instructors. This programme has proven to establish a sustainable empowerment model that can be replicated within community-based religious education networks.